TRANSFORMATIONAL LEADERSHIP AS A MEDIATOR BETWEEN REWARD SYSTEMS AND LECTURER PERFORMANCE AT SEKOLAH TINGGI FARMASI INDONESIA - Ali Gusliana; Muji Rahayu (RADJA PUBLIKA, 2026)
This study aims to analyze the mediating role of transformational leadership in the relationship between the reward system and lecturer performance at the Indonesian College of Pharmacy. The study used a quantitative approach with an explanatory research design . The study population was all permanent and non-permanent lecturers totaling 100 people who were selected as respondents through a saturated sampling technique. Data analysis was conducted using mediation regression (path analysis) to test the direct and indirect effects between variables . The results of the hypothesis test indicate that the reward system directly has a positive and significant effect on transformational leadership and lecturer performance. Transformational leadership has a positive and significant effect on performance. Likewise, transformational leadership is proven to mediate the influence of the reward system on employee performance. This study provides theoretical contributions in the development of human resource management models in higher education as well as practical implications for the management of reward policies and institutional leadership in a sustainable manner.